Cases Report the Cronkhite-Canada Syndrome: Improving the Prognosis. Issue 52 (December 2015) - Yu, Yi Qun; Whorwell, Peter James; Wang, Lin Heng; Li, Jun Xiang; Chang, Qing; Meng, Jie
Abstract : Abstract: Cronkhite-Canada syndrome (CCS) is a rare nongenetic polyposis syndrome first reported by Cronkhite and Canada in 1955. 1 Up to the present time, the literature consists of ∼400 cases of CCS with the majority being reported from Japan 2 although 49 cases have been described in China. 3 CCS is characterized by diffuse polyposis of the digestive tract in association with ectodermal changes, such as onychomadesis, alopecia, and cutaneous hyperpigmentation. The principal symptoms of CCS are diarrhea, weight loss, abdominal pain, and other gastrointestinal complications, such as protein-losing enteropathy and malnutrition. It has been traditional to consider that CCS is associated with a poor prognosis. This paper describes a relatively mild case and reviews the literature, which more recently, suggests that it may be a more benign condition that might actually be reversible with treatment. There is some evidence that infection or disturbed immunity may be involved in the pathophysiology and that targeting such abnormalities could have therapeutic potential. A strong case could be made for establishing an international case registry for this disease so that the pathophysiology, treatment, and prognosis could become much better understood.